Psikologi Komunikasi Humas Aceh dalam Menyikapi Pandemi Korona Covid : (Analisis Pemberitaan Penyediaan Kuburan Masal oleh Pemerintah Aceh) - Eva Khairani (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
Since early 2020 news and information about the Covid-19 outbreak in Aceh has been the target of the public. One source of news is the Aceh government's public relations. As a source of reference information about this pandemic, every word chosen in mass communication becomes important. From some of the news delivered by the Aceh government, the news about the provision of mass graves is causing controversy, this is certainly interesting to study. Psychology of communication is very influential in the process of delivering messages, the effectiveness of communication that is built is also an interesting thing to be associated with the situation. If the choice of words for the preparation of mass graves is changed to the provision of special graves for covid-19 sufferers, then the response that will be given by the public will be different. The fact is that the Aceh government does not yet understand the psychology of effective communication, so the message delivered has caused public unrest.